2018
DOI: 10.1039/c8ta05569f
|View full text |Cite
|
Sign up to set email alerts
|

A hydrophobic surface enabled salt-blocking 2D Ti3C2MXene membrane for efficient and stable solar desalination

Abstract: A general strategy for hydrophobic 2D Ti3C2MXene membrane fabrication for efficient and stable solar desalination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
243
0
7

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(256 citation statements)
references
References 43 publications
2
243
0
7
Order By: Relevance
“…1 Solar energy is considered as a green, inexhaustible, and viable energy resource that can be used in a variety of fields, such as photovoltaics, photosynthesis, and solar thermal conversion. [5][6][7][8][9] Therefore, in order to achieve higher solar-tovapor conversion efficiency and improve water evaporation rate, researchers are paying more and more attention to designing a new type of solar steam generation system, which can minimize heat loss during the heating process and enhance the solar-to-vapor conversion efficiency. [2][3][4] Although solar energy is a promising source of energy, the low efficiency of solar-to-steam conversion has greatly hampered the practical application of solar energy, such as solar evaporation and water desalination, because of the large amount of optical and systemic heat loss in conventional distillation processes.…”
Section: Introductionmentioning
confidence: 99%
“…1 Solar energy is considered as a green, inexhaustible, and viable energy resource that can be used in a variety of fields, such as photovoltaics, photosynthesis, and solar thermal conversion. [5][6][7][8][9] Therefore, in order to achieve higher solar-tovapor conversion efficiency and improve water evaporation rate, researchers are paying more and more attention to designing a new type of solar steam generation system, which can minimize heat loss during the heating process and enhance the solar-to-vapor conversion efficiency. [2][3][4] Although solar energy is a promising source of energy, the low efficiency of solar-to-steam conversion has greatly hampered the practical application of solar energy, such as solar evaporation and water desalination, because of the large amount of optical and systemic heat loss in conventional distillation processes.…”
Section: Introductionmentioning
confidence: 99%
“…[95] As expected, the evaporation rate of janus evaporator was almost invariable after 45 min running, indicating excellent salt-resistant ability, whereas the evaporation rate of conventional evaporator (i.e., hydrophilic solar absorber) slowed down by 15% because of obvious salts accumulation on the surface observed in SEM images. In addition, hydrophobic trimethoxy(1H,1H,2H,2H-perfluorodecyl)silane (PFDTMS) [142] and poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT-PSS) [143] were also used to modify d-Ti 3 C 2 nanosheets and carbon materials to prepare hydrophobic solar absorbers, respectively, endowing the water evaporator with excellent saltresistant ability applied in long-term solar desalination. In order to minimize the adverse effects on evaporation, hydrophobic modified layers or technologies need to obey some features as follows: 1) enough transparent hydrophobic layers to enable intrinsic optical property without any losses, 2) conformal function of hydrophobic layers to prevent the clogging of the inherent channels, ensuring adequate water supplies and fast release of vapors.…”
Section: Strategies For Enhancing Water Evaporation Efficiencymentioning
confidence: 99%
“…b) Schematic illustration of the salt‐blocking Ti 3 C 2 membrane based evaporation device . Reproduced with permission . Copyright 2018, Royal Society of Chemistry.…”
Section: Photothermal Evaporationmentioning
confidence: 99%
“…The pervaporation membrane fabricated using Ti 3 C 2 was first reported by Liu et al The hydrophilic property was found to give a high water flux through an efficient salt rejection process . The evaporation performance of the hydrophobic Ti 3 C 2 MXene membranes are further investigated by Zhao et al The Ti 3 C 2 MXene is modified by trimethoxy silane, and commercial filter membrane is used for water supply (Figure b). Thanks to the high light‐conversion ability, surface engineering, and abundant water supply channels, a remarkable solar evaporation performance can be obtained, including high solar steam‐conversion efficiency of 71% and evaporation rate of 1.31 kg m −2 h −1 .…”
Section: Photothermal Evaporationmentioning
confidence: 99%
See 1 more Smart Citation